PENGARUH HARGA DAN BRAND IMAGE TERHADAP MINAT MENGINAP DI BOBOCABIN - Christabella Eilin Setyawan; Basilius Agung Eka Saputra Assa; Nabila Salsabila Samodro; Hendra (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to determine the influence of price and brand image on consumer interest in staying at Bobocabin. The study uses a quantitative approach with data collected through structured questionnaires from respondents aged 17–50 years. The results of multiple linear regression analysis show that both price and brand image have a positive and significant effect on the intention to stay at Bobocabin. The coefficient of determination (R²) is 0.808, indicating that 80.8% of the variation in stay intention can be explained by price and brand image. These findings suggest that competitive pricing and a strong brand image are key factors in attracting consumer interest. Keywords : Price, Brand Image, Interest in staying, Bobocabin